Use of Monte Carlo simulations in the assessment of calibration strategies – Part II: design of a software package (CalEval). (April 2013) - Burrows, John
Background: Calibration curves for use in chromatographic bioassays are normally constructed using least squares regression analysis. However, the effects of changes in the number and distribution of calibrators, together with the choice between linear and nonlinear regressions and their associated weighting factors, are difficult to quantify.Results/discussion: A Monte Carlo simulation software package is under development that uses the assay range, concentration versus response relationship and intra-assay measurement precision profile to quantify the errors resulting from different calibration procedures. Criteria for assay batch acceptance, in terms of calibrator and QC sample estimates being within specified limits, are included in the design.Conclusion: Monte Carlo software provides a means to evaluate calibration strategies and maximize assay batches meeting acceptance criteria.